Whole blood omega-3 fatty acid concentrations are inversely associated with blood pressure in young, healthy adults. Issue 7 (July 2018) - Filipovic, Mark G.; Aeschbacher, Stefanie; Reiner, Martin F.; Stivala, Simona; Gobbato, Sara; Bonetti, Nicole; Risch, Martin; Risch, Lorenz; Camici, Giovanni G.; Luescher, Thomas F.; von Schacky, Clemens; Conen, David; et al.
Abstract : Background: Omega-3 fatty acids ( n − 3 FA) may have blood pressure (BP)-lowering effects in untreated hypertensive and elderly patients. The effect of n − 3 FA on BP in young, healthy adults remains unknown. The Omega-3 Index reliably reflects an individuals' omega-3 status. We hypothesized that the Omega-3 Index is inversely associated with BP levels in young healthy adults. Methods: The current study ( n = 2036) is a cross-sectional study investigating the baseline characteristics of a cohort, which includes healthy adults, age 25–41 years. Individuals with cardiovascular disease, known diabetes or a BMI higher than 35 kg/m 2 were excluded. The Omega-3 Index was determined in whole blood using gas chromatography. Association with office and 24-h BP was assessed using multivariable linear regression models adjusted for potential confounders. Results: Median Omega-3 Index was 4.58% (interquartile range 4.08; 5.25). Compared with individuals in the lowest Omega-3 Index quartile, individuals in the highest had a SBP and DBP that was 4 and 2 mmHg lower, respectively ( P < 0.01). A significant linear inverse relationship of the Omega-3 Index with 24-h and office BP was observed. Per 1-U increase in log-transformed Omega-3 Index the lowering in BP (given as multivariable adjusted β coefficients; 95% confidence interval) was −2.67 mmHg (−4.83; −0.51; P = 0.02) and −2.30 mmHg (−3.92; −0.68; P = 0.005) for 24-h SBP and DBP, respectively. Conclusion: A higher Omega-3 Index is associated with statistically significant, clinically relevant lower SBP and DBP levels in normotensive young and healthy individuals. Diets rich in n − 3 FA may be a strategy for primary prevention of hypertension. Abstract : Supplemental Digital Content is available in the text